2014
DOI: 10.3748/wjg.v20.i35.12431
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures and colorectal cancers: A quantitative overview of epidemiological evidence

Abstract: A traditional belief widespread across the biomedical community was that dietary habits and genetic predisposition were the basic factors causing colorectal cancer. In more recent times, however, a growing evidence has shown that other determinants can be very important in increasing (or reducing) incidence of this malignancy. The hypothesis that environmental and occupational risk factors are associated with colorectal cancer is gaining ground, and high risks of colorectal cancer have been reported among work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 117 publications
1
39
1
Order By: Relevance
“…These agents were selected for analysis because of their probable association with colorectal cancer, based on previous research 7. We categorised the agents into five groups: solvents (toluene, aromatic hydrocarbon solvents, methylene chloride, aliphatic and alicyclic hydrocarbon solvents); combustion products (diesel exhaust emissions, gasoline exhaust emissions, benzo(a)pyrene, polycyclic aromatic hydrocarbons, welding fumes); metals (chromium, iron, nickel, lead); dusts (animal dust, asbestos, quartz, wood dust); and other (formaldehyde).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents were selected for analysis because of their probable association with colorectal cancer, based on previous research 7. We categorised the agents into five groups: solvents (toluene, aromatic hydrocarbon solvents, methylene chloride, aliphatic and alicyclic hydrocarbon solvents); combustion products (diesel exhaust emissions, gasoline exhaust emissions, benzo(a)pyrene, polycyclic aromatic hydrocarbons, welding fumes); metals (chromium, iron, nickel, lead); dusts (animal dust, asbestos, quartz, wood dust); and other (formaldehyde).…”
Section: Methodsmentioning
confidence: 99%
“…The studies that have been done have found associations between colorectal cancer risk and different occupational groups such as textile industry workers, firefighters, automobile workers,7 petrochemical industry workers,8 beverage industry workers, iron and steel workers, dockyard workers9–11 and railway employees 12. Most of these studies described the association with job categories rather than occupational agents.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the results of studies concerning the associations between the level of toxic metals and metallic agents with either pathological tumor features and disease outcome or cancer risk, have been contradictory, and no firm conclusions can be drawn from them (Basu et al, 2013;Oddone et al, 2014;Park et al, 2012;Sivulka and Seilkop, 2009). Moreover, a literature survey reveals only individual studies related to these parameters in head and neck region neoplasms and none to sinonasal inverted papilloma (Akinmoladun et al, 2013;Kosova et al, 2012;Starska et al, 2014a).…”
Section: Introductionmentioning
confidence: 94%
“…Exposure to these inorganics in the form of free ions, metal complexes, metal particles and poorly-soluble compounds occurs most often during inhalation from environmental and occupational sources at workplaces and through ingestion. Metal toxicity in humans may also be related to iatrogenic or genetic factors (Crisponi, 2014;Oddone et al, 2014;Tokar et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…An inverse relationship between fish consumption and colorectal cancer was found in most previous studies [29], whereas the relationship between red meat consumption and colorectal cancer remains a subject of scientific debate. This association is possibly weak in magnitude and heterogeneous across the subgroup analyses [30]. Obesity is linked with an increased risk of colon cancer in men; however, the association is less consistent in women [31].…”
Section: Discussionmentioning
confidence: 91%